Electoral System of India: Major Issues and Challenges - MANZOOR BHAT, RASHID; Showkat Ahmad Dar; Aadil Ahmad Shairgojri (RADJA PUBLIKA, 2022)
Modern democracy, or representative democracy, is the subject of this paper. Voters or Electors are the ones who cast ballots, and we'll analyse the merits and demerits of universal adult franchise. The current electoral system does not provide adequate representation for all voters, resulting in a large number of votes being cast in vain. However, a proportional representation system does exist. A candidate has been proclaimed victorious in state assembly elections where the margin of victory was less than 100 votes. Unless there is some unusual circumstance, a candidate usually wins an election with only 30 to 35 percent of the total votes cast. As a result, he or she cannot be considered the result of a popular vote. As the world's most populous democracy, the United States will be the focus of this investigation.